IMPLEMENTASI PERMAINAN EDUKASI COVID 19 UNTUK MENURUNKAN KECEMASAN PADA ANAK SEKOLAH DI ERA PANDEMI COVID 19 - Margiyati Margiyati; Ainnur Rahmanti; Afifah Kurniawati; Diska Darma Putri (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2021)
Children are at risk of experiencing anxiety due to the Covid 19 pandemic. Children's anxiety due to the Covid-19 pandemic because there is a lot of unclear information circulating, feeling that this pandemic is not over so they can't go out, bored at home, lack of time to socialize and play with friends friends, and the stress of online learning. Giving play therapy is one of the nursing interventions that can reduce anxiety in children. This study uses quantitative research methods with a quasi-experimental research design with a pre-test and post-test design approach. The inclusion criteria set were children aged 8-11 years, experiencing mild-moderate anxiety, in good health. The intervention was carried out 4 times using the covid 19 educational game media. Observation of anxiety was carried out twice, namely before the intervention and after the intervention. The number of samples is 24 school children. The questionnaire used to measure the level of anxiety of preschool-aged children with the Spence Children's Anxiety Scale (SCAS). Analysis of the data in this study used a statistical test with a significance level of 0.05 using the sample paired T-test. The results of the statistical test show that there is a significant effect between the implementation of the covid 19 educational game and the anxiety of school-age children in the era of the covid 19 pandemic. The implementation of the covid 19 educational game is recommended in handling children's anxiety by involving the family.